Analisis Hubungan Kepuasan Kerja Dan Komitmen Organisasional Terhadap Turnover Intensions Di Matahari Department Store Plaza Medan Fair - Yoseph P Hutabarat (Jurnal Manajemen Dan Akuntansi Medan, 2020)
Many things are pointed out as the cause of the discharge of an employee from a job . Employment situation faced today is not in accordance with the desired expectations (onset of dissatisfaction in work) or influenced by the views of employees to obtain alternative jobs and a better satisfaction .The Increasing of employee who happened to come out of Matahari Department Store in Plaza Medan Fair , especially at the operational employees cashier and sales clerk . The purpose of this study was to analyze the relationship between job satisfaction and organizational commitment to turnover intentions in Matahari Department Store Plaza Medan Fair and formulates policies as efforts to reduce the number of employees who quit in Matahari Department Store Plaza Medan Fair. Questionnaire data that has been collected is processed with Multiple Regression Analysis. The analysis showed that job satisfaction is a factor closely related to turnover intensions , while the factors of organizational commitment has no significant relationship with turnover intensions